More than Merely Transcription: An Analysis of Metatasks and Twitter Chat. Issue 2 (June 2016) - Rosenfeld, Christine
This article seeks to understand the practices that digital volunteers of the Smithsonian's Transcription Center (TC) engage in aside from transcribing. A thematic analysis of the Twitter feed @TranscribeSI demonstrates that volunteers are doing much more than just transcribing; they are additionally engaging in critical archival practices regarding reflexivity and filling in gaps in the historical record. Museums that hope to foster deep engagement among volunteers and to create a sustained community of virtual museumgoers may wish to model their digital initiatives on those of the TC. Doing so will ensure that museums move beyond mere data extraction toward building complex relationships with audiences through online initiatives.